Consumption of ultra-processed foods among children up to two years old in the North and Northeast regions of Brazil: An integrative review (Research, Society and Development, 2025)
High consumption of ultra-processed foods (UPF) in infants can have short-, medium-, and long-term consequences. Growth deficits, obesity, and the development of chronic noncommunicable diseases may occur. Therefore, the objective of this study was to review the literature about the consumption of ultra-processed foods among infants, focusing on the North and Northeast regions of the country, in order to comprehensively understand the average age and determining factors for the introduction of these foods. A total of 431 articles were identified, of which 422 articles were excluded in the screening and by exclusion criteria. Thus, 9 original studies were included in this review. Of the total articles, 5 articles carried out cross-sectional studies and 4 articles were cohort studies. Regarding the average age of introduction of UPF, only two studies reported it, and both with the same average of 6 months. There is a prevalent consumption of UPF in the Northeast and North regions of the country. In several states in the Northeast, this is mainly associated with low income, low education and insufficient breastfeeding (exclusive or supplementary). In addition, in the North region there is a critical consumption of UPF by the indigenous population related to contact with people outside the family environment and eating habits that are different from those culturally observed. However, this prevalent eating behavior of high UPF consumption is subject to change, as long as there is action planning and the viability of structural public and social policies.